The Microfinance Business Model: Enduring Subsidy and Modest Profit - Cull, Robert; Demirgüç-Kunt, Asli; Morduch, Jonathan (Published by Oxford University Press on behalf of the World Bank, 2019)
Recent evidence suggests only modest social and economic impacts of microfinance. Favorable cost-benefit ratios then depend on low costs. This paper calculates the costs of microcredit and other elements of the microcredit business model using proprietary data on 1,335 microfinance institutions between 2005 and 2009, jointly serving 80.1 million borrowers. The costs of making small loans to poorer clients are high, and when revenues fall short of costs, subsidies are necessary to deliver services to those clients on a sustainable basis. Using a method that accounts for the opportunity costs of all forms of subsidy, the analysis finds that the median institution receives five cents of subsidy per dollar lent and $51 of subsidy per borrower (in PPP-adjusted terms). Relatively low levels of median subsidy suggest that even modest benefits of microcredit could yield impressive cost-benefit ratios. The distribution of subsidies is highly skewed, however: the average subsidy per dollar lent is 13 cents, and the average subsidy per borrower is $248. The data show that subsidies per borrower are substantially higher for commercial microfinance banks and some non-bank financial institutions that make relatively large loans. MFIs organized as non-governmental organizations (NGOs), in contrast, generally rely less on subsidy.